DEIXIS IN X (2014) ALBUM OF ED SHEERAN’S SONG - Ichwan Choise Pandapotan Sirait; Amrin Saragih (State University of Medan, 2015)
This study deals with the types of deixis in x (2014) album of Ed Sheeran’s song.The objectives of the study were to describe the kinds of deixis in x (2014) albumof Ed Sheeran’s song which were used in song lyrics, finding out the mostdominant kind and why it is dominantly used. This research applied descriptivequalitative research. Descriptive qualitative research is a method which haspurpose to make a description of situation, condition, phenomenon, and intend toaccumulative data (Cresswell : 2001), this research uses descriptive qualitativeresearch to describe deixis in X (2014) album of Ed Sheeran’s Songs. The sourceof data was song lyrics by Ed Sheeran. Searching the song lyrics as the instrumentto collect the data and there were twelve song. Based on the analysis, there werefive kinds of deixis were found in that album, they are person, spatial, temporal,discourse and social deixis. It consists of 746 person deixis (62.1%), 111 spatialdeixis (9.2%), 157 temporal deixis (13.1%), 108 discourse deixis (9%) and 80social deixis (6.6%).The most dominat kind of deixis which is used in the albumis person deixis with total 746 or 62.1%. the deictic word “I” is the most dominantword of person deixis in the album. Person deixis is dominantly used because hemostly wrote his own experiences into the song lyrics.